The role of physiotherapy in preventing falls in the elderly - Queiroz, Gabriel de Souza; Raimundo, Ronney Jorge de Souza; Lima, Keite Oliveira de (JRG Journal of Academic Studies, 2024)
Introduction: This study's main objectives were to identify the main challenges of falls in elderly people and the perspectives of finding possible solutions to remedy or alleviate the difficulties of this fall in the lives of elderly people, as well as highlighting the perspectives of treatment. Objectives: the main objective is to show the importance of practicing different activities for the elderly, which will be demonstrated in a bibliographical research, considering activities for the elderly to be important. With the importance of promoting adequate and satisfactory health for the elderly. Aging healthily and contributing to a better quality of life is a fundamental point of this study. Methodology: The methodology was a bibliographic review that starts from the principle of analyzing and compiling studies already published by authors in the area, for which searches were carried out on several websites such as Scileo Brasil. Results: they went through the stages of carrying out this, such as: data collection, reading of articles related to the topic, the written part and the presentation of the results in accordance with the authors and the objectives proposed in this theoretical and secure basis. Conclusion: It is extremely important to investigate the development of scientific studies that address the topic and/or even prove the importance of different activities with the help of professionals in the area of ​​physiotherapy for the elderly.